High-Performance Aqueous Electrolyte Symmetrical Supercapacitor using Porous Carbon Derived Cassava Peel Waste - Erman Taer; Harahap Eva Wahyuni; Apriwandi Apriwandi; Taslim Rika (AMTS and Faculty of Engineering - Universitas Riau, 2022)
Electrolytes have been generally recognized as one of the most important components in enhancing the electrochemical performance of supercapacitors. On the other hand, aqueous electrolytes are considered prime candidates for the development of the next generation of symmetric supercapacitors due to their low-cost, environmentally friendly, high ionic conductivity, fine ionic size, and high capacitance. Herein, the symmetrical supercapacitor of the sustainable porous carbon-based electrode material was confirmed through various aqueous electrolytes consisting of neutral, basic, and acidic Na2SO4, KOH, and H2SO4. Activated carbon is obtained from high potential biomass sources of cassava peel waste. Activated carbon synthesis was performed with a comprehensive approach in order to obtain abundant pore structure, high porosity, and improved wettability through a combination of high-temperature chemical and physical activation. in addition, the electrode material is designed to resemble a solid disc without the addition of a synthetic binder. The evaluation of the disc dimensions showed high porosity in the obtained activated carbon. Furthermore, the symmetrical supercapacitor of the optimized electrode material exhibit excellent specific capacitances of 112, 150, and 183 F g-1 at 1 mV s-1 in the electrolytes Na2SO4, KOH, and H2SO4, respectively. In addition, the highest rate capability of 70% was confirmed in the H2SO4 acid electrolyte. Moreover, their coulombic efficiency can be maintained around 89% with low equivalent series resistance 0.21-0.42 ?. Therefore, the activated carbon-based supercapacitor symmetric cell device from cassava peel shows high performance for developing high-performance supercapacitor applications with guaranteed stability in aqueous electrolytes.